Sosialisasi Peranan Generasi Muda dalam Pariwisata Danau Toba kepada Siswa SMKN1 Simanindo - Kennedy, Posma Sariguna Johnson (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Lake Toba is a strategic tourist destination in Indonesia with rich natural and cultural potentials. The local cultural wisdom serves as one of the primary attractions for visitors. The government encourages the active role of the local community in managing and developing tourism. In this regard, the younger generation, especially millennials, plays a central role in advancing tourism and preserving cultural heritage. Despite their pivotal role, millennials face various challenges, including shifting towards more modern development, lack of commitment, and the influence of gadgets in daily life. Therefore, this initiative aims to enhance the role of the younger generation in the development of tourism in Lake Toba by conducting lectures and outreach at SMK Negeri 1 Simanindo. The proposed solutions include training, leveraging technology, and partnering with local governments. With the active involvement of Young Generations, Lake Toba is expected to become a high-quality and sustainable tourist destination, providing significant economic and social benefits to the region and the country as a whole.